Macroecological predictors to determine future refuges of Luciobarbus species in the Tigris–Euphrates basin: Rethinking conservation strategies and management - Hadi Khoshnamvand; Seyed Mohsen Mousavi; Asef Darvishi; Kourosh Ahmadi; Amir Naghibi; Karel Janko; Asghar Abdoli; Faraham Ahmadzadeh (Global Ecology and Conservation)
Freshwater ecosystems, being highly susceptible to the impacts of climate change, experience a greater influence than terrestrial and marine ecosystems. Hence, by identifying the regions that will be most affected by climate change in the future, managers can implement more efficient and effective measures to protect them. In this study, we utilized six Luciobarbus species residing at the southernmost boundary of their global distribution as a representative species model. We aimed to evaluate the influence of climate change on the distribution of these key species to identify potential future climate refuges within the Tigris–Euphrates basin and use the richness mapping method to determine the most critical driver of their richness pattern for high-priority conservation. In the current study, using an ensemble approach, we modeled the potential impact of climate change on the distributions of six Luciobarbus species by the years 2061–2080 and 2081–2100 under two Shared Socio-economic Pathways (SSPs) of general circulation models (GCMs). We employed a generalized linear model (GLM) with a quasi-Poisson distribution to create a map depicting the richness of Luciobarbus fish species.Our projections indicate that suitable habitats will decline in both time series under climate change SSP126 and SSP585 scenarios, resulting in the loss of certain habitat patches in the Southwest of Iran, Syria and Iraq. The result of the species richness map shows the southern region of the Tigris–Euphrates basin has the highest number of species. Furthermore, temperature was the most critical predictor of Luciobarbus fish richness in the basin. Implementing significant strategies, such as identifying areas with the highest species richness and susceptibility to climate change, is essential to conserving and managing key species like Luciobarbus. Additionally, establishing protected areas in suitable landscapes and preserving critical habitat patches as future climate refuges are crucial. These measures will contribute significantly to the conservation and management of freshwater species.